原发性肺淋巴瘤1例 (Zhongguo Fei Ai Za Zhi, 2014)
Primary pulmonary lymphoma (PPL) is an extranodally original disorder, which is involving the lung parenchyma and (or) bronchial with clonal lymph cell abnormal proliferation. PPL is very rare in clinics, accounting for only 0.5%-1% of primary lung tumors, and can easily be misdiagnosed or missed due to the nonspecifically clinical features and imaging findings. Although the treatment of this disease has controversial, surgery and postoperative adjuvant chemotherapy are used for most patients in present. This review will report a rare case of primary pulmonary lymphoma, and discuss its diagnosis and treatment.